The Challenges before Corporate Social Responsibility in Global Era. - Mr. Gaurav, Mr. Gaurav (International Journal of Scientific Research and Management (IJSRM), 2015)
Corporate Social Responsibility has played a vital role in the development of Indian economy. It has captured significant attention of managers and executives especially at multinational and multi-divisional firms. However, links between CSR’s drivers (strategic planning, firm culture) and corporate social responsibility (CSR) have seen little or no empirical verification, particularly in India. The present study aims to test the challenges before CSR. This study considers formal strategic planning and humanistic culture as drivers of CSR. Information was collected by secondary data. With the help of the data it can be concluded that CSR has to face a lot of challenges in global era but it crate lots of opportunity for Indian economy.